Markell and Voge's medical parasitology - John, David T.; Petri, William A.
Featuring line drawings and halftones that provide visual examples related directly to the textual material, this title explores the etiologic agents of human disease belonging to the animal kingdom: protozoa, helminths, and arthropods, all of which are a significant cause of, or link to illness encountered in tropical and temperate environments